Analysis of the names of accommodation establishments in Bulgaria. Issue 3 (3rd July 2022) - Ivanov, Stanislav; Seyitoğlu, Faruk; Dimitrova, Fani
ABSTRACT: This paper identifies the categories of accommodation establishments' names in Bulgaria and determines the role of a property's characteristics (category, location, type, and size/capacity) on the chosen name using a quantitative approach. The findings indicate that male, female, and family names, and names indicating geographic toponyms, represent nearly half of all names. Plants, emotions, and quality-related words are also widely used. Furthermore, results reveal that category, location, size, and type of establishment influence the naming of establishments. In addition, the findings illustrate that Bulgarian names prevail in the naming of establishments. Binary logistic regression reveals that urban, higher category, and larger properties are more likely to have foreign names. The theoretical and destination marketing implications are discussed as well.